Research on the Commercialization and Productive Protection of the Atlas Silk: A Case Study of Two Atlas Garment Factories - Wu, Yunqing (Transactions on Economics, Business and Management Research, 2024)
In 2008, Atlas Silk was recorded as a National Intangible Cultural Heritage. However, although the government has multi-facetedly supported it, its commercialization still has many difficulties. Through field research and in-depth interviews with the inheritors in two Atlas silk garment factories, this paper will elaborate on the challenges of the commercialization of Atlas Silk and the dilemma of income for its inheritors. Enterprises study the market expansion results from industrial production, which is based on attracting consumers’ attention, especially from the general public and younger people. However, on another level, this kind of production devalues the real value of Atlas Silk material. Apart from that, a very small income earned by its craftsmen has put it into a severe crisis of sustaining from generation to generation for its inheritors. This contradiction can be solved by enterprises using innovative market strategies to give Atlas handicrafts more value and develop more room for inheritors’ income, thus realizing a balance between cultural preservation and commercial development.